Investigation of Using Plastic Waste in Asphalt Concrete Mixture as Binder Modifier - ABDUL AZIZ, MUHAMMAD AZHAN; Shamshuddin, Mustafa Kamal (Recent Trends in Civil Engineering and Built Environment, 2021)
Indirect tensile strength test (ITS) have been performed as performance testof asphalt concrete mixture according to Marshall standard gradation type AC14.There is a detrimental environmental effect of plastic waste products. The reuse ofplastic waste will enhance the properties in engineering construction projects such asroad paving bitumen and mixtures of asphalt. In order to decrease harmful of plasticwaste to the environment, it have been reused in asphalt concrete mixture as aggregatereplacement. The purpose of this study is to investigate the suitability of using plasticwaste in asphalt concrete mixture and to evaluate the durability of asphalt mixturewith plastic waste. This scope focused on the parameters of indirect tensile strength.The plastic waste used in this study was in the form of granules of about 3 mmdiameter which PET type mineral bottles and the proportion used for this study about0.2, 0.4 and 0.6% of percentage plastic waste. Method that had been used in this studywas indirect tensile strength test with Marshall procedure to conduct the study. Theresult from the performed test showed that plastic waste also suitable for asphaltmodifier in certain percentage such as less than 0.2%. This is because of more percentof plastic was added, it will reduce the durability of the asphalt concrete due to losethe original characteristics of asphalt concrete mixture but it still relevant to use asasphalt modifier in order to create potential to reduce the pollution. Utilization ofplastic waste was satisfying for asphalt concrete performance. For therecommendation, the plastic waste to be used as a modifier in asphalt concrete mustnot exceed 0.2 percent as it will reduce the durability of asphalt concrete mixture.Performing another more tests in detail using same percentage of 0.2% to obtain morecriteria with respect to the decrease in durability of the asphalt concrete.